A Generalisation of Contraction Principle in Metric Spaces. (11th January 2009) - Dutta, P. N.; Choudhury, Binayak S.
Abstract : Here we introduce a generalisation of the Banach contraction mapping principle. We show that the result extends two existing generalisations of the same principle. We support our result by an example.